Restorative justice and the relationship of perpetrator and victim of crime - Bulatović Aleksandra (Temida, 2015)
Restorative justice as the theoretical foundation of social reaction to crime is one of the key themes of contemporary criminological discourse. The idea of crime as a conflict between perpetrator and victim of crime is included in the core ideas related to the concept of restorative justice, which differs from traditional understanding of crime as a relationship between the state and the individual. This change in perspective on crime points towards social reaction to crime that differs from traditional criminal justice system. As the restoration process of relationship damaged by crime is directly related to possibilities of participation in the very process, institutionalisation of that participation sets the scope of restorative process. In this article, the author points towards the traditional criminal justice and restorative justice processes, focusing the relationship of perpetrator and victim of crime and the process of conflict resolution. The aim of the article is to highlight the conflict perspective as a defining element of the relationship between offender and victim, and to underline the effectiveness of restorative justice as social reaction to crime, which contributes to optimisation of the relationship between the offender and the community.